Supremasi Perempuan Dalam Novel Renjana Dyana Karya Adimodel : Kajian Feminisme Radikal - Fadhlur Rahman; Juanda Juanda; Suarni Syam Saguni (Interference: Journal of Language, Literature, and Linguistics, 2021)
This study aims to describe the form of supremacy shown by female characters and the factors that cause female characters to become radical in the novels being analyzed. This research is descriptive qualitative in nature. The data of this research are in the form of words, phrases, sentences, and paragraphs that reveal the contents of the story in the novel. The data source of this research is the novel Renjana Dyana by Adimodel published by Elex Media Komputindo in 2015. The approach used is the study of radical feminism. The results of this study indicate that first, the form of supremacy shown by the female character in the novel Renjana Dyana is the effort of the Dyana character to make a change in society to end and destroy all male power which is represented in the form of freedom of attitude, action and thought as well as character courage. Dyana takes a fight against men from the aspect of sexuality. Second, apart from women's supremacy, there are factors that cause female characters in Adimodel's Renjana Dyana to become radical, triggered by three factors, namely patriarchy, religion, and economic conditions.